Cancer Informatics in 2018: The Mysteries of the Cancer Genome Continue to Unravel, Deep Learning Approaches the Clinic, and Passive Data Collection Demonstrates Utility - Warner, Jeremy L.; Patt, Debra; Section Editors for the IMIA Yearbook Section on Cancer Informatics (Yearbook of Medical Informatics, 2019)
Objective: To summarize significant research contributions on cancer informatics published in 2018.Methods: An extensive search using PubMed/Medline, Google Scholar, and manual review was conducted to identify the scientific contributions published in 2018 that address topics in cancer informatics. The selection process comprised three steps: (i) 15 candidate best papers were first selected by the two section editors, (ii) external reviewers from internationally renowned research teams reviewed each candidate best paper, and (iii) the final selection of four best papers was conducted by the editorial board of the International Medical Informatics Association (IMIA) Yearbook.Results: The four selected best papers present studies addressing many facets of cancer informatics, with immediate applicability in the translational and clinical domains.Conclusion: Cancer informatics is a broad and vigorous subfield of biomedical informatics. Progress in cancer genomics, artificial intelligence, and passively collected data is especially notable in 2018.
Keywords: Neoplasms; informatics; health information technology; genomics; ontologies